Flexible PC lens for isolating positive pressure protective clothing and preparation method thereof
Patent Information
- Application Number
- CN202611270133.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]因此,亟需开发一种兼具优异柔性、长效防雾性能、高透明度和良好耐候性的PC镜片,专用于隔绝式正压防护服的透明视窗,以解决现有技术中镜片易起雾、防雾涂层易失效、柔性不足、耐久性差等技术难题
1、优异的柔韧性和耐弯折性能:本发明通过在PC基材层中引入增韧改性剂,显著降低了PC的刚性和脆性,使镜片在0.3~1.2mm的薄厚度下仍具有出色的柔韧性,能够适应不同头型的弯曲弧度,且在反复弯折后不产生折痕、应力发白或裂纹,满足正压防护服镜片的使用需求。
Smart Images

Figure CN122997441A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of personal protective equipment technology, specifically to a flexible PC lens for an isolation positive pressure protective suit and its preparation method. Background Technology
[0002] Positive pressure isolation suits (also known as positive pressure biological protective suits or medical positive pressure protective suits) are full-body protective gear consisting of the main body of the suit, a transparent hood, and an air supply hose system. Their core protective mechanism involves continuously supplying purified gas into the suit through the air supply system, creating a positive pressure environment where the internal pressure is 5-20 Pa higher than the external environment. This effectively blocks the intrusion of biological pathogens, radioactive aerosols, and other contaminants. These suits are widely used in medical and epidemic prevention, nuclear, biological, and chemical contamination protection, and emergency rescue. Related products must comply with industry standards such as YY 1887-2023 "Medical Positive Pressure Protective Suit".
[0003] In existing technologies, the transparent viewing window (face shield) of positive pressure protective suits is typically made of polycarbonate (PC). While PC material boasts excellent transparency and impact resistance, fogging is highly likely to occur on the inner surface of the face shield during actual use. The main reasons for fogging are: 1) The protective suit has excellent airtightness, causing water vapor generated by human respiration and movement to accumulate inside the garment. Furthermore, the exhaust valves designed to maintain positive pressure have some airflow resistance, leading to water vapor stagnation in the head area; 2) The inner surface temperature of the PC lens is lower than the temperature of the air and fabric inside the suit, causing water vapor to condense on the lens surface due to the temperature difference, resulting in fogging. Fogging of the lens severely obstructs the wearer's vision, affecting normal medical care, emergency rescue, and other operations, and even posing safety hazards.
[0004] To address the fogging problem of protective clothing lenses, some solutions already exist in the prior art. For example, Chinese patent "A Positive Pressure Anti-fog Face Mask and Protective Clothing with the Face Mask" (Patent No. ZL202120917630) discloses a positive pressure anti-fog face mask that uses an air inlet at the top of the mask to blow away fog through a transparent viewing window. However, this type of solution relies on continuous airflow; if the air supply system malfunctions or the air volume is insufficient, the anti-fog effect is greatly reduced. Another solution, such as Chinese patent "A Method for Preparing Wear-Resistant Anti-fog PC Optical Lenses" (Patent Application No. 202410287756), discloses a method for coating a composite precursor fluid onto the surface of a PC lens to form an anti-fog coating. However, such coatings are mainly designed for spectacle lenses, and their flexibility and bending resistance are insufficient to meet the repeated bending requirements of protective clothing lenses during use. In addition, existing anti-fog coatings generally suffer from insufficient durability. Under prolonged wear, repeated wiping, and high temperature and humidity conditions, the coating is prone to failure due to mechanical wear, swelling and leaching of hydrophilic components, or decreased adhesion.
[0005] More importantly, there is currently no dedicated material solution for the lenses of self-contained positive pressure protective suits. Positive pressure protective suit lenses not only require excellent transparency and anti-fog performance, but also good flexibility to adapt to the curvature of different head shapes, and the ability to withstand repeated bending during donning, doffing, folding, and storage without creases, cracks, or coating peeling. Furthermore, positive pressure protective suits are typically used for extended periods (e.g., continuous wear for 4-12 hours), requiring stable anti-fog performance in humid and hot environments. In addition, in extreme application scenarios such as nuclear, biological, and chemical contamination, the lenses must also possess chemical corrosion resistance and self-cleaning capabilities.
[0006] Therefore, there is an urgent need to develop a PC lens that combines excellent flexibility, long-lasting anti-fog performance, high transparency and good weather resistance, specifically for transparent windows in isolation positive pressure protective clothing, in order to solve the technical problems of easy fogging of lenses, easy failure of anti-fog coatings, insufficient flexibility and poor durability in existing technologies. Summary of the Invention
[0007] Based on the above-mentioned prior art, the present invention provides a flexible PC lens for isolation positive pressure protective clothing and its preparation method. The lens of the present invention uses toughened and modified polycarbonate (PC) as the substrate, and the surface is coated with a double-layer functional coating consisting of an adhesive layer and a hydrophilic anti-fog layer, thus having good flexibility, excellent anti-fog performance and durability.
[0008] The technical solution adopted to achieve the above-mentioned objectives of this invention is as follows: In a first aspect, the present invention provides a flexible PC lens for an isolation positive pressure protective garment, comprising a flexible PC substrate layer, at least one surface of the flexible PC substrate layer having an adhesive layer, and a hydrophilic anti-fog layer being provided on the surface of the adhesive layer facing away from the flexible PC substrate layer. The flexible PC substrate layer is made of toughened modified polycarbonate resin; The adhesive layer is made from (meth)acrylate copolymer, polyurethane acrylate and silane coupling agent, and is cured to form the adhesive layer. The hydrophilic antifog layer is made of hydrophilic polymers, inorganic nanoparticles and crosslinking agents, and is formed by curing.
[0009] Furthermore, the thickness of the flexible PC substrate layer is 0.3–1.2 mm, the thickness of the adhesive layer is 0.5–5 μm, and the thickness of the hydrophilic anti-fog layer is 2–15 μm.
[0010] Furthermore, an adhesive layer and a hydrophilic anti-fog layer are sequentially disposed on both the inner and outer surfaces of the flexible PC substrate layer. The anti-fog layer on the inner surface of the flexible PC substrate layer mainly prevents water vapor generated by the wearer's breathing and sweat from condensing and fogging; the anti-fog layer on the outer surface of the flexible PC substrate layer has anti-fog, self-cleaning and anti-pollution functions, and can further improve the lens's chemical corrosion resistance.
[0011] Furthermore, the flexible PC substrate layer comprises the following raw materials in parts by weight: 70-90 parts of polycarbonate resin, 5-20 parts of toughening modifier, 0.1-1 parts of antioxidant, 0.1-0.8 parts of light stabilizer, and 0.1-0.5 parts of processing aid.
[0012] The introduction of toughening modifiers can significantly improve the flexibility and bending resistance of PC substrates while maintaining their transparency. This allows the lenses to maintain sufficient mechanical strength even when the thickness is reduced to 0.3–1.2 mm, and they are less prone to stress whitening or creases during repeated bending.
[0013] Furthermore, the toughening modifier is selected from at least one of polyurethane elastomers (such as TPU), polyester elastomers (such as TPEE), methyl methacrylate-butadiene-styrene copolymer (MBS), and acrylate core-shell toughening agents.
[0014] Furthermore, the toughening modifier is selected from a composition of polyurethane elastomer and acrylate core-shell toughening agent, wherein the mass ratio of polyurethane elastomer to acrylate core-shell toughening agent is 1:0.5 to 1:2. More preferably, the toughening modifier is a combination of polyurethane elastomer (TPU) and acrylate core-shell toughening agent, wherein the mass ratio of the two is 1:1, and the total addition amount is 10 to 15 parts.
[0015] Furthermore, the antioxidant is selected from a compound system of hindered phenolic antioxidants and phosphite antioxidants. Preferably, the hindered phenolic antioxidants are selected from antioxidants 1010, 1076, etc., and the phosphite antioxidants are selected from antioxidants 168, 626, P-EPQ, etc.
[0016] Furthermore, the light stabilizer is selected from hindered amine light stabilizers (HALS) (Tinuvin 770, Chimassorb 944, etc.) or benzotriazole ultraviolet absorbers (UV-234, UV-326, UV-327, etc.).
[0017] Furthermore, the processing aid is selected from calcium stearate, zinc stearate, or silicone lubricants (such as Dow Corning MB50-001 and RN4-7081).
[0018] Furthermore, the adhesive layer comprises the following raw materials in parts by weight: 40-65 parts of (meth)acrylate copolymer, 15-35 parts of polyurethane acrylate, 3-10 parts of silane coupling agent, 1-5 parts of initiator, and 20-50 parts of diluent A.
[0019] The core function of the adhesive layer is to form a chemical bond with the PC substrate surface through the silane coupling agent, and to generate good interfacial compatibility and mechanical interlocking with the top hydrophilic anti-fog layer through the flexibility of the polyurethane acrylate segments, thereby effectively relieving interlayer stress and preventing the coating from cracking or peeling when subjected to bending deformation.
[0020] Furthermore, the glass transition temperature of the (meth)acrylate copolymer is 30–60°C, and the weight-average molecular weight is 50,000–150,000. Preferably, the (meth)acrylate copolymer is selected from DEGALAN. ® LP 64 / 12, Paraloid TM B-44, DIANA TM BR-106, etc.
[0021] Furthermore, the polyurethane acrylate is an aliphatic polyurethane acrylate oligomer with a functionality of 2-4, exhibiting excellent flexibility and adhesion. Preferably, the polyurethane acrylate is selected from ETERMER 6112-100, ETERMER 6112-100, Desmolux® U 200, EBECRYL® 8800, etc.
[0022] Further, the silane coupling agent is selected from at least one of aminosilane, epoxysilane, and methacryloxysilane. Preferably, the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane (KH550), γ-glycidoxypropyltrimethoxysilane (KH560), and γ-methacryloyloxypropyltrimethoxysilane (KH570), and more preferably, the silane coupling agent is KH570.
[0023] Further, the initiator is selected from at least one of α-hydroxy ketones, acylphosphine oxides, acid catalysts, and organometallic catalysts. Preferably, the initiator is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone (Irgacure 1173), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (Irgacure 819), p-toluenesulfonic acid (Nacure 2500), and dibutyltin dilaurate. More preferably, the initiator is selected from α-hydroxy ketones, specifically Irgacure 1173.
[0024] Further, the diluting solvent A is selected from one or more of water, esters, alcohols, and ether alcohols. Preferably, the diluting solvent A is selected from at least one of ethyl acetate and isopropanol. Preferably, the diluting solvent A is a combination of ethyl acetate and isopropanol, with an ethyl acetate / isopropanol volume ratio of 1:1.
[0025] Furthermore, the hydrophilic antifog layer comprises the following raw materials in parts by weight: 30-60 parts of hydrophilic polymer, 5-20 parts of inorganic nanoparticles, 5-15 parts of crosslinking agent, 1-5 parts of initiator, and 30-70 parts of diluent B.
[0026] Furthermore, the hydrophilic polymer is selected from at least one of polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyethylene glycol (PEG) diacrylate, polyacrylic acid (PAA), and hyaluronic acid. Preferably, the hydrophilic polymer is a combination of polyvinylpyrrolidone and polyethylene glycol diacrylate in a mass ratio of 1:0.3 to 1:1. Polyvinylpyrrolidone provides excellent hydrophilicity and film-forming properties, while polyethylene glycol diacrylate forms a stable three-dimensional network structure through photocuring crosslinking, preventing the hydrophilic components from swelling and leaching during use.
[0027] Furthermore, the inorganic nanoparticles are selected from one or more of nano-silica (SiO2), nano-titanium dioxide (TiO2), and nano-zinc oxide (ZnO), with a particle size of 10–50 nm. Preferably, the inorganic nanoparticles are a combination of nano-silica and nano-titanium dioxide, with a mass ratio of 1:0.2 to 1:0.5. The introduction of nano-silica can significantly improve the surface hardness and wear resistance of the coating; nano-titanium dioxide not only further enhances the mechanical properties but also endows the coating with a certain photocatalytic self-cleaning ability, which helps degrade organic pollutants adhering to the lens surface in nuclear, biological, and chemical protection scenarios.
[0028] Furthermore, the crosslinking agent is selected from at least one of hexamethoxymethyl melamine, polyisocyanate crosslinking agents, glutaraldehyde, and boric acid. Preferably, the crosslinking agent is hexamethoxymethyl melamine. The crosslinking agent undergoes a crosslinking reaction with the active groups such as hydroxyl and amine groups in the hydrophilic polymer to form a dense hydrophilic network structure, which enhances the water resistance and scrub resistance of the coating while ensuring high hydrophilicity.
[0029] Furthermore, the initiator is the same as that used in the adhesive layer.
[0030] Further, the diluting solvent B is selected from one or more of water, alcohols, and ether alcohols. Preferably, the diluting solvent B is selected from at least one of deionized water and isopropanol. Preferably, the diluting solvent is a combination of deionized water and isopropanol, with a deionized water / isopropanol volume ratio of 2:1.
[0031] Secondly, the present invention also provides a method for preparing the above-mentioned flexible PC lens for isolation positive pressure protective clothing, comprising the following steps: S1. Plasticize and extrude the raw material for preparing the flexible PC substrate layer to obtain modified PC granules. Extrude the modified PC granules into a casting or calendering form, and cut them to obtain the flexible PC substrate layer. S2. The flexible PC substrate layer is cleaned and activated sequentially; S3. Dissolve the (meth)acrylate copolymer, polyurethane acrylate and silane coupling agent in a diluent, then add the initiator and mix evenly to obtain the adhesive coating. S4. Disperse the hydrophilic polymer, inorganic nanoparticles and crosslinking agent in a diluent, then add an initiator and mix thoroughly to obtain a hydrophilic antifog coating. S5. Apply the adhesive coating to at least one surface of the flexible PC substrate layer treated in step S2, pre-dry it, and then cure it to form an adhesive layer. S6. Apply the hydrophilic anti-fog coating to the surface of the adhesive layer facing away from the flexible PC substrate, pre-dry it, and then cure it to form a hydrophilic anti-fog layer. S7. Anneal the three-layer structure obtained in step S6 to obtain the flexible PC lens for the isolation positive pressure protective clothing.
[0032] Furthermore, the specific operation method of step S1 is as follows: Polycarbonate resin, toughening modifier, antioxidant, light stabilizer, and processing aids are mixed evenly according to weight, and added to a twin-screw extruder. The mixture is then melt-blended, extruded, and granulated at 240–280°C to obtain modified PC granules. The resulting modified PC granules are then extruded and cast at an extrusion temperature of 260–270°C, a casting roll temperature of 80–90°C, and a traction speed of 3–5 m / min to obtain flexible PC substrate sheets with a thickness of 0.3–1.2 mm, which are then cut to the required dimensions.
[0033] Furthermore, in step S2, the cleaning process uses anhydrous ethanol or isopropanol as the cleaning solvent and ultrasonic cleaning for 5 to 10 minutes to remove surface oil and impurities.
[0034] Furthermore, in step S2, the activation treatment employs plasma treatment or ultraviolet ozone treatment, preferably plasma treatment, with a plasma power of 100–300W and a treatment time of 30–120 seconds. More preferably, the plasma treatment power is 150–200W and the treatment time is 60–90 seconds. Activation treatment can introduce active groups such as hydroxyl and carboxyl groups onto the PC surface, improving the adhesion of subsequent coatings.
[0035] Furthermore, the specific operation method of step S3 is as follows: Dissolve the (meth)acrylate copolymer, polyurethane acrylate and silane coupling agent in a diluted solvent according to the mass ratio, stir evenly, add photoinitiator or thermal initiator, continue stirring until completely dissolved, filter through a 0.5μm filter membrane to obtain the adhesive layer coating.
[0036] Furthermore, the specific operation method of step S4 is as follows: The hydrophilic polymer, inorganic nanoparticles, and crosslinking agent are dispersed in a diluent according to the mass ratio. The dispersion is carried out at 1000-3000 rpm for 20-40 minutes using a high-speed disperser to obtain a uniform dispersion. Subsequently, a photoinitiator or thermal initiator is added to the dispersion, stirred evenly, and filtered through a 0.5 μm filter membrane to obtain a hydrophilic anti-fog coating.
[0037] Furthermore, the inorganic nanoparticles are pre-treated with a silane coupling agent to modify their surface, thereby enhancing their dispersion stability in the coating.
[0038] Furthermore, before applying the adhesive layer, the flexible PC substrate layer treated in step S2 is subjected to electrostatic dust removal to ensure surface cleanliness.
[0039] Furthermore, in step S5, the coating is performed using dip coating, spray coating, or roller coating processes, and the coating thickness is controlled to be 5–20 μm wet film thickness.
[0040] Furthermore, in step S6, the coating is performed using dip coating, spray coating, or roller coating processes, and the coating thickness is controlled to be 10–30 μm wet film thickness.
[0041] Furthermore, in steps S5 and S6, the pre-drying method is as follows: pre-dry at 60-80°C for 3-5 minutes to remove most of the solvent.
[0042] Furthermore, in steps S5 and S6, the curing is performed by ultraviolet light curing or thermal curing. The ultraviolet light curing conditions are: ultraviolet light wavelength 365–395 nm, irradiation energy 500–1500 mJ / cm². 2 The curing time is 10-30 seconds; the heat curing conditions are: heat curing in an oven at 80-120℃ for 15-30 minutes.
[0043] Furthermore, the ultraviolet curing is preferably carried out under a nitrogen protective atmosphere to reduce the oxygen inhibition effect and improve the curing quality of the coating surface.
[0044] Furthermore, the annealing treatment method is as follows: the three-layer structure obtained in step S6 is annealed in a constant temperature oven at 40-60°C for 2-4 hours to eliminate internal stress in the coating and further improve the adhesion between the coating and the substrate.
[0045] Furthermore, when it is necessary to sequentially apply an adhesive layer and a hydrophilic anti-fog layer to both the inner and outer surfaces of the flexible PC substrate, a process of sequentially coating and curing one side before sequentially coating and curing the other side, or a process of simultaneous double-sided dip coating, can be adopted.
[0046] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. Excellent flexibility and bending resistance: By introducing a toughening modifier into the PC substrate layer, this invention significantly reduces the rigidity and brittleness of PC, enabling the lens to maintain excellent flexibility even with a thickness of 0.3 to 1.2 mm. It can adapt to the curvature of different head shapes and does not produce creases, stress whitening or cracks after repeated bending, thus meeting the requirements for the use of lenses in positive pressure protective clothing.
[0047] 2. Long-lasting and stable anti-fogging performance: The hydrophilic anti-fogging layer of this invention utilizes a three-dimensional cross-linked network constructed from hydrophilic polymers and cross-linking agents, combined with the reinforcing effect of inorganic nanoparticles. This results in a water contact angle of ≤15°, exhibiting superhydrophilic properties. It can rapidly spread condensate into a uniform water film rather than discrete water droplets, effectively preventing light scattering and maintaining lens clarity and transparency. The cross-linked structure effectively inhibits the swelling and leaching of hydrophilic components, ensuring stable anti-fogging performance under prolonged use, repeated wiping, and humid and hot environments.
[0048] 3. High interfacial bonding strength: The adhesive layer of this invention acts as a "buffer bridge" between the PC substrate layer and the hydrophilic anti-fog layer. On the one hand, it forms a chemical bond with the activated PC surface through a silane coupling agent; on the other hand, the flexibility of the polyurethane acrylate segments forms good interfacial compatibility and mechanical interlocking with the hydrophilic anti-fog layer. During bending and deformation, the adhesive layer can effectively absorb and disperse interfacial stress, preventing coating cracking and peeling.
[0049] 4. Excellent comprehensive optical performance: By optimizing the formulation and process of the PC substrate layer, adhesive layer and hydrophilic anti-fog layer, the present invention produces a flexible PC lens with a transmittance of ≥88% and a haze of ≤2.0% in the visible light wavelength range, which meets the requirements of positive pressure protective clothing for clear vision and complies with the requirements of industry standards such as YY 1887-2023 for the optical performance of transparent windows.
[0050] 5. Multifunctional integration: The nano-titanium dioxide introduced into the hydrophilic antifog layer of this invention endows the lens with photocatalytic self-cleaning function, which can degrade organic pollutants attached to the lens surface under light conditions, which is of great significance in extreme application scenarios such as nuclear, biological and chemical pollution; at the same time, the hydrophilic antifog layer has good chemical corrosion resistance and can resist the erosion of common disinfectants and cleaning agents.
[0051] 6. Excellent overall performance: Through the synergistic design of a toughened and modified PC substrate layer and a dual-layer functional coating of hydrophilic anti-fog layer and adhesive layer, this invention enables flexible PC lenses to achieve a light transmittance of ≥88% and a haze of ≤2.0% in the visible light wavelength range, a water contact angle of ≤15°, and no surface cracks and a light transmittance retention rate of ≥95% after 1000 bends with a bending radius of 50mm. This solves the problems of easy fogging, insufficient flexibility and poor coating durability of existing positive pressure protective clothing lenses.
[0052] 7. Stable process and suitable for industrial production: The preparation method of this invention has clear process parameters and strong controllability. The equipment and materials used are easy to obtain, making it suitable for large-scale continuous production and showing good prospects for industrial application. Attached Figure Description
[0053] Figure 1 This is a schematic diagram of the flexible PC lens structure of the isolation positive pressure protective clothing of Example 1.
[0054] Among them, 1-flexible PC substrate layer, 2-adhesive layer, 3-hydrophilic anti-fog layer. Detailed Implementation
[0055] The present invention will now be described in detail with reference to specific embodiments, but these embodiments are not to be construed as limiting the scope of protection of the present invention in any sense.
[0056] The sources of some of the raw materials used in the following examples and comparative examples are as follows: The polycarbonate resin used is bisphenol A type, with a melt index of 10 g / 10 min, specifically Covestro Makrolon. ® 2805; The thermoplastic polyurethane elastic TPU uses TPU with a Shore hardness of 85A, specifically Lubrizol Estane. ® 58277; Acrylic core-shell toughening agents of the MBS type are used, specifically Dow Paraloid. TM EXL-2314; methyl methacrylate-butyl acrylate-hydroxyethyl methacrylate copolymer: specifically using DEGALAN ® LP64 / 12N, Tg=58℃, weight-average molecular weight 68000; The aliphatic polyurethane acrylate oligomers are oligomers with a functionality of 2, specifically using Changxing ETERMER6112-100.
[0057] Example 1
[0058] A type of isolation positive pressure protective clothing with flexible PC lenses includes a flexible PC substrate layer 1. Adhesive layers 2 are provided on both the inner and outer surfaces of the flexible PC substrate layer 1. Hydrophilic anti-fog layers 3 are provided on the surfaces of both adhesive layers 2 facing away from the flexible PC substrate layer. Figure 1 As shown.
[0059] The raw materials for the flexible PC substrate layer include, by weight, polycarbonate resin (Covestro Makrolon). ® 2805) 80 parts, thermoplastic polyurethane elastomer TPU (Lubrizol Estane) ® 58277) 6 copies, MBS (PARALOID) TM EXL-2314 6 parts, antioxidant 1010 0.3 parts, antioxidant 168 0.2 parts, hindered amine light stabilizer (Chimassorb 944) 0.3 parts, zinc stearate 0.2 parts.
[0060] The adhesive layer comprises, by weight, methyl methacrylate-butyl acrylate-hydroxyethyl methacrylate copolymer (DEGALAN). ® The ingredients are: 50 parts of LP 64 / 12N, 25 parts of aliphatic polyurethane acrylate oligomer (Changxing ETERMER6112-100), 5 parts of γ-methacryloyloxypropyltrimethoxysilane (KH570), 3 parts of photoinitiator Irgacure 1173, and 40 parts of diluent A. Diluent A is a mixed solvent formed by uniformly mixing ethyl acetate and isopropanol in a volume ratio of 1:1.
[0061] The raw materials for the hydrophilic antifog layer include, by weight: 8 parts of nano-silica (particle size 20nm), 2 parts of nano-titanium dioxide (particle size 25nm), 35 parts of polyvinylpyrrolidone (K30), 15 parts of polyethylene glycol diacrylate (molecular weight 600), 3 parts of initiator Irgacure 1173, 8 parts of hexamethoxymethyl melamine (HMMM), and 50 parts of diluent B. Diluent B is a mixed solvent formed by uniformly mixing deionized water and isopropanol at a volume ratio of 2:1.
[0062] The preparation method of the flexible PC lens for the aforementioned isolation positive pressure protective clothing is as follows: 1. Preparation of flexible PC substrate layer: Polycarbonate resin, thermoplastic polyurethane elastomer (TPU), MBS, antioxidant 1010, antioxidant 168, hindered amine light stabilizer, and zinc stearate were added to a high-speed mixer and mixed evenly according to the specified parts by weight. The resulting mixture was then fed into a twin-screw extruder, with the barrel temperatures set as follows: Zone 1 250℃, Zone 2 260℃, Zone 3 265℃, Zone 4 260℃, and die head 255℃. The mixture was melt-blended, extruded, cooled, and granulated to obtain modified PC granules.
[0063] Modified PC granules were formed by a single-screw extrusion casting machine. The temperature of the casting machine barrel was set as follows: Zone 1 260℃, Zone 2 265℃, Zone 3 265℃, Zone 4 260℃, and Die Head 260℃. The casting roller temperature was 85℃, and the traction speed was 4m / min. A flexible PC substrate sheet with a thickness of 0.5mm was obtained, which was then cut into 200mm×300mm lens blanks to obtain the flexible PC substrate layer.
[0064] 2. Pretreatment of the flexible PC substrate layer: The flexible PC substrate layer was first ultrasonically cleaned with anhydrous ethanol for 5 minutes, then rinsed with deionized water, and subsequently dried with nitrogen. The cleaned flexible PC substrate layer was then surface activated using an oxygen plasma treatment device with a treatment power of 200W and a treatment time of 60 seconds.
[0065] 3. Preparation of adhesive layer coating: The methyl methacrylate-butyl acrylate-hydroxyethyl methacrylate copolymer, aliphatic polyurethane acrylate oligomer (functionality=2) and γ-methacryloyloxypropyltrimethoxysilane (KH570) were dissolved in diluent A according to the weight ratio. After stirring until completely dissolved, the photoinitiator Irgacure 1173 was added and stirring was continued until homogeneous. Finally, the mixture was filtered through a 0.5 μm filter membrane to obtain the adhesive coating.
[0066] 4. Preparation of hydrophilic antifog coating: Eight parts of nano-silica (particle size 20 nm) and two parts of nano-titanium dioxide (particle size 25 nm) were added to a mixed solvent of 90 parts ethanol and 10 parts deionized water and ultrasonically dispersed for 30 minutes to obtain a nanoparticle dispersion.
[0067] Separately, 1.5 parts of γ-methacryloxypropyltrimethoxysilane (KH570) were dissolved in a mixed solvent of 10 parts of ethanol and water (ethanol / water = 9:1, v / v, pH 4.5), and the mixture was stirred and hydrolyzed for 30 minutes. Then, it was slowly added to the nanoparticle dispersion and stirred at a constant temperature of 60°C for 3 hours. After the reaction was completed, the resulting reaction product was centrifuged, and the solid was washed with ethanol to obtain surface-modified nanoparticles.
[0068] Surface-modified nanoparticles, polyvinylpyrrolidone (K30), and polyethylene glycol diacrylate (M n 600) Hexamethoxymethyl melamine was added to diluent B and dispersed at high speed at 2000 rpm for 30 minutes. Then, 3 parts of photoinitiator Irgacure 1173 were added, stirred evenly, and filtered through a 0.5 μm filter membrane to obtain a hydrophilic anti-fog coating.
[0069] 5. Coating and curing of the adhesive layer: The flexible PC substrate layer, pretreated in step 2, is immersed in the adhesive coating and pulled up at a uniform speed of 100 mm / min, with the wet film thickness controlled at 10 μm. The coated flexible PC substrate layer is then pre-baked in a 70°C oven for 4 minutes, and then placed in a UV curing device under nitrogen protection with an irradiation wavelength of 365 nm and an irradiation energy of 800 mJ / cm². 2 6. Coating and curing of the hydrophilic anti-fog layer: Curing is performed under ultraviolet light for 15 seconds to form an adhesive layer. The double-layer structure obtained in step 5 was immersed in a hydrophilic anti-fog coating and pulled up at a uniform speed of 80 mm / min, with the wet film thickness controlled at 15 μm. The coated double-layer structure was pre-baked in a 70℃ oven for 4 minutes, and then placed in a UV curing device under nitrogen protection with an irradiation wavelength of 365 nm and an irradiation energy of 800 mJ / cm². 2 It is cured for 15 seconds under ultraviolet light to form a hydrophilic anti-fog layer.
[0070] 7. Annealing treatment: The three-layer structure obtained in step S6 is placed in a 50°C constant temperature oven for annealing for 3 hours and then naturally cooled to room temperature to obtain the flexible PC lens for the isolation positive pressure protective clothing.
[0071] Example 2
[0072] The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that the toughening modifier in the raw materials of the flexible PC substrate layer is 12 parts of polyester elastomer (TPEE), and no MBS toughening agent is added.
[0073] Example 3
[0074] The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that the hydrophilic antifog layer uses a combination of 30 parts of polyvinyl alcohol (PVA, degree of alcoholysis 88%) and 20 parts of polyethylene glycol diacrylate (molecular weight 600) as the hydrophilic polymer and 6 parts of glutaraldehyde as the crosslinking agent.
[0075] Example 4
[0076] The formulation and preparation method are basically the same as those in Example 1, except that the adhesive layer and the hydrophilic antifog layer are cured by thermosetting. The thermosetting conditions are as follows: after dip coating, pre-bake at 80°C for 5 minutes, and then place in an oven at 100°C for 20 minutes for curing.
[0077] Example 5
[0078] The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that the thickness of the flexible PC substrate layer is 0.8 mm, and the inorganic nanoparticles in the hydrophilic antifog layer are 10 parts of nano-silica.
[0079] Comparative Example 1 The formulation and preparation method are basically the same as those in Example 1, except that a hydrophilic anti-fog layer is not provided.
[0080] Comparative Example 2 The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that no adhesive layer is set, and the hydrophilic anti-fog coating is directly applied to the two surfaces of the plasma-treated flexible PC substrate layer.
[0081] Comparative Example 3 The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that no toughening modifier is added to the raw materials of the flexible PC substrate layer.
[0082] Comparative Example 4 It uses commercially available ordinary PC protective face shield lens (1.0mm thick, without anti-fog coating).
[0083] Comparative Example 5 The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that aliphatic polyurethane acrylate oligomer (Changxing ETERMER 6112-100) is not added in the preparation of the adhesive layer.
[0084] Comparative Example 6 The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that no silane coupling agent KH570 is added in the preparation of the adhesive layer.
[0085] Comparative Example 7 The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that no inorganic nanoparticles (nano silica and nano titanium dioxide) are added in the preparation of the hydrophilic antifog layer.
[0086] Comparative Example 8 The formulation and preparation method are basically the same as those in Example 1. The difference from Example 1 is that in the preparation of the hydrophilic antifog layer, only 50 parts of polyvinylpyrrolidone (PVP) are used as the hydrophilic polymer, and polyethylene glycol diacrylate is not added.
[0087] Performance testing The PC lenses of Examples 1-5 and Comparative Examples 1-8 were tested for the following performance parameters: 1) Light transmittance and haze: The test was conducted in accordance with GB / T 2410-2008 "Determination of transmittance and haze of transparent plastics", using a haze meter to measure the light in the visible wavelength range (380-780nm).
[0088] 2) Water contact angle: Using a contact angle meter, 2 μL of deionized water was dropped onto the lens surface, and the static water contact angle was measured. Five points were measured for each sample, and the average value was taken.
[0089] 3) Anti-fog performance: Place the lens 5cm above a 50℃ constant temperature water bath, exposing the lower surface of the lens to water vapor for 30 seconds. Immediately observe the fogging on the lens surface and take a photo to record the results. Evaluation criteria: "Excellent" is recorded as the lens remains transparent and fog-free; "Good" is recorded as the lens fogs slightly but is still transparent; "Poor" is recorded as the lens fogs severely and is not transparent.
[0090] 4) Adhesion: The cross-cut test was conducted according to GB / T 9286-2021 "Paints and Varnishes Cross-cut Test". The coating cut spacing was 1 mm. The peel test was conducted using 3M 600 tape and evaluated on a scale of 0 to 5, with 0 being the best (no peeling).
[0091] 5) Bending resistance: Bending the lens onto a cylindrical surface with a radius of curvature of 50mm, holding for 3 seconds and releasing, repeating this bending cycle 1000 times. After bending, visually inspect the surface for cracks and test the light transmittance retention rate. Light transmittance retention rate = (light transmittance after bending / initial light transmittance) × 100%.
[0092] 6) Wear resistance: According to GB / T 17657-2013, the coating haze change was tested using a Taber abrasion tester with a CS-10F grinding wheel, a load of 500g, and 100 rotations.
[0093] 7) Resistance to damp heat aging: The lens was placed in a constant temperature and humidity chamber at 85℃ and 85% relative humidity for 168 hours. After removal, the changes in water contact angle and anti-fog performance were tested.
[0094] The test results are shown in Table 1 below: Table 1 Performance Test Results
[0095] The test results in the table above show that: 1. The flexible PC lenses obtained in Examples 1-5 all exhibit excellent comprehensive performance: light transmittance ≥89%, haze ≤1.5%, water contact angle ≤12°, anti-fog performance all reach "excellent" level, and adhesion is all at level 0. This shows that the dual-coating structure of the adhesive layer and hydrophilic anti-fog layer and the corresponding formulation design provided by the present invention can effectively endow PC lenses with anti-fog function while maintaining good optical performance.
[0096] 2. Bending test results show that the light transmittance retention of the flexible PC lenses in Examples 1-5 is ≥96% after bending, and there are no surface cracks. However, the light transmittance retention of the PC lens in Comparative Example 2 (without adhesive layer) is only 91.3% after bending, and slight cracks appear, indicating that the adhesive layer plays a crucial role in stress buffering and interface protection during bending deformation. The light transmittance retention of the PC lens in Comparative Example 3 (without toughening modifier) drops to 82.5% after bending, and obvious creases appear. This shows that toughening modification of the PC substrate is crucial for the flexibility and bending resistance of PC lenses.
[0097] 3. Damp heat aging tests showed that after 168 hours of treatment at 85°C and 85%RH, the water contact angle of the flexible PC lenses in Examples 1-5 only increased slightly, and their anti-fog performance remained basically unchanged. However, the water contact angle of the PC lens in Comparative Example 2 increased significantly from 11° to 25°, and its anti-fog performance decreased significantly. This was because the lack of an adhesive layer allowed moisture to penetrate along the interface under humid conditions, leading to a decrease in the adhesion of the hydrophilic anti-fog layer and the loss of hydrophilic components. Comparative Example 1 (without an anti-fog layer) itself did not have an anti-fog function, and its water contact angle was as high as 72°.
[0098] 4. Comparative Example 4 (commercially available ordinary PC screen) has acceptable light transmittance, but high haze (2.5%), large water contact angle (68°), poor anti-fog performance, obvious creases after bending, and significantly inferior abrasion resistance compared to the PC lenses of Examples 1-5.
[0099] 5. In Comparative Example 5, the adhesive coating did not contain aliphatic polyurethane acrylate oligomer (Changxing ETERMER6112-100), resulting in poor material flexibility and a decrease in light transmittance retention after bending, but still better than Comparative Example 3. At the same time, the lack of aliphatic polyurethane acrylate oligomer weakened the interfacial interaction, leading to a decrease in adhesion.
[0100] 6. In Comparative Example 6, without the addition of silane coupling agent KH570 to the adhesive layer coating, the interface relies solely on physical adsorption. The bottom adhesive layer adheres to the PC substrate only through weak interactions such as van der Waals forces and hydrogen bonds, lacking chemical bond anchoring, leading to decreased adhesion. Simultaneously, water molecules in a humid and hot environment possess extremely strong penetrating power, gradually seeping into the interface between the coating and the substrate. Water molecules accumulate at the interface, forming a hydration layer on the PC substrate surface, weakening and replacing the original physical adsorption, resulting in localized blistering and micro-peeling of the coating. Once the top hydrophilic anti-fog layer loses the support and fixation of the bottom adhesive layer, the coating structural integrity is compromised, surface roughness increases, and hydrophilic groups cannot spread evenly. Therefore, after humid and hot aging, the water contact angle increases significantly, and the anti-fog performance deteriorates.
[0101] 7. In Comparative Example 7, no inorganic nanoparticles were added to the hydrophilic antifog coating. The absence of inorganic nanoparticles firstly significantly reduced the wear resistance of the surface coating, thus greatly increasing the haze after grinding. Secondly, the lack of inorganic nanoparticles (especially titanium dioxide) caused the coating to swell excessively and lose hydrophilic components during humid heat aging, resulting in a significant increase in the water contact angle after humid heat aging.
[0102] 8. In Comparative Example 8, the hydrophilic antifog coating did not contain polyethylene glycol diacrylate. Relying solely on PVP, a stable insoluble cross-linked network could not be formed, leading to a large amount of hydrophilic active substances dissolving during humid heat aging. Therefore, the water contact angle increased significantly after humid heat aging, resulting in poorer antifog performance. These three failure modes in Comparative Examples 6-8, from different perspectives, demonstrate that the three-layer synergistic design of this invention—chemical bonding anchoring (coupling agent), physical reinforcement framework (nanoparticles), and chemical cross-linked network (multi-component hydrophilic polymer and cross-linking agent)—is indispensable. The absence of any one of these components will cause the coating to fail rapidly under harsh humid heat conditions.
[0103] In summary, the flexible PC lens provided by this invention achieves a balance of flexibility, anti-fog performance, and durability through the synergistic design of "toughened modified PC substrate + dual-functional coating of adhesive layer and hydrophilic anti-fog layer," which is significantly superior to existing technical solutions and can meet the needs of isolation positive pressure protective clothing under various harsh usage conditions.
[0104] Industrial applicability The flexible PC lens for isolation positive pressure protective clothing and its manufacturing method provided by this invention have the following industrial applicability: 1) All raw materials used are commercially available industrial products, with wide sources and stable supply; 2) The manufacturing process is based on mature extrusion molding, coating and photocuring / thermal curing technologies, requiring no special equipment and suitable for direct implementation on existing protective equipment production lines; 3) The product can be widely used in the manufacture of transparent windows for medical positive pressure protective clothing, nuclear, biological and chemical protective clothing, emergency rescue protective clothing, etc. It can also be promoted to other personal protective equipment fields such as protective masks and goggles, with broad market prospects.
Claims
1. A flexible PC lens for a type of isolation positive pressure protective clothing, characterized in that: It includes a flexible PC substrate layer, at least one surface of the flexible PC substrate layer is provided with an adhesive layer, and a hydrophilic anti-fog layer is provided on the surface of the adhesive layer facing away from the flexible PC substrate layer. The flexible PC substrate layer is made of toughened modified polycarbonate resin; The adhesive layer is made from (meth)acrylate copolymer, polyurethane acrylate and silane coupling agent, and is cured to form the adhesive layer. The hydrophilic antifog layer is made of hydrophilic polymers, inorganic nanoparticles and crosslinking agents, and is formed by curing.
2. The flexible PC lens for the isolation positive pressure protective clothing according to claim 1, characterized in that: The thickness of the flexible PC substrate layer is 0.3–1.2 mm, the thickness of the adhesive layer is 0.5–5 μm, and the thickness of the hydrophilic anti-fog layer is 2–15 μm.
3. The flexible PC lens for the isolation positive pressure protective clothing according to claim 1, characterized in that: An adhesive layer and a hydrophilic anti-fog layer are sequentially provided on both the inner and outer surfaces of the flexible PC substrate layer.
4. The flexible PC lens of the isolation positive pressure protective clothing according to claim 1, characterized in that... The flexible PC substrate layer comprises the following raw materials in parts by weight: 70-90 parts of polycarbonate resin, 5-20 parts of toughening modifier, 0.1-1 parts of antioxidant, 0.1-0.8 parts of light stabilizer, and 0.1-0.5 parts of processing aid.
5. The flexible PC lens for the isolation positive pressure protective clothing according to claim 4, characterized in that: The toughening modifier is selected from at least one of polyurethane elastomers, polyester elastomers, methyl methacrylate-butadiene-styrene copolymers, and acrylate core-shell toughening agents.
6. The flexible PC lens for the isolation positive pressure protective clothing according to claim 4, characterized in that: The toughening modifier is selected from a composition of polyurethane elastomer and acrylate core-shell toughening agent, and the mass ratio of polyurethane elastomer to acrylate core-shell toughening agent is 1:0.5 to 1:
2.
7. The flexible PC lens for isolation positive pressure protective clothing according to claim 1, wherein the adhesive layer comprises the following raw materials in parts by weight: 40-65 parts of (meth)acrylate copolymer, 15-35 parts of polyurethane acrylate, 3-10 parts of silane coupling agent, 1-5 parts of initiator, and 20-50 parts of diluent A.
8. The flexible PC lens for the isolation positive pressure protective clothing according to claim 7, characterized in that: The glass transition temperature of the (meth)acrylate copolymer is 30-60°C, and the weight-average molecular weight is 50,000-150,000. The polyurethane acrylate is an aliphatic polyurethane acrylate oligomer with a functionality of 2 to 4. The silane coupling agent is selected from at least one of aminosilane, epoxysilane, and methacryloxysilane.
9. The flexible PC lens of the isolation positive pressure protective clothing according to claim 1, characterized in that... The hydrophilic antifog layer comprises the following raw materials in parts by weight: 30-60 parts hydrophilic polymer, 5-20 parts inorganic nanoparticles, 5-15 parts crosslinking agent, 1-5 parts initiator, and 30-70 parts diluent B.
10. The flexible PC lens for the isolation positive pressure protective clothing according to claim 9, characterized in that: The hydrophilic polymer is selected from at least one of polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol diacrylate, polyacrylic acid, and hyaluronic acid; The inorganic nanoparticles are selected from at least one of nano-silica, nano-titanium dioxide, and nano-zinc oxide, with a particle size of 10-50 nm. The crosslinking agent is selected from at least one of hexamethoxymethyl melamine, polyisocyanate crosslinking agent, glutaraldehyde, and boric acid.
11. A method for preparing a flexible PC lens for an isolation positive pressure protective garment as described in any one of claims 1-10, characterized in that... Includes the following steps: S1. Plasticize and extrude the raw materials for preparing the flexible PC substrate layer to obtain modified PC granules. Extrude the modified PC granules into a casting or calendering form, and cut them to obtain the flexible PC substrate layer. S2. Clean and activate the flexible PC substrate layer; S3. Dissolve the (meth)acrylate copolymer, polyurethane acrylate and silane coupling agent in a diluent, then add the initiator and mix evenly to obtain the adhesive coating. S4. Disperse the hydrophilic polymer, inorganic nanoparticles and crosslinking agent in a diluent, then add an initiator and mix thoroughly to obtain a hydrophilic antifog coating. S5. Apply the adhesive coating to at least one surface of the flexible PC substrate layer treated in step S2, pre-dry it, and then cure it to form an adhesive layer. S6. Apply the hydrophilic anti-fog coating to the surface of the adhesive layer facing away from the flexible PC substrate, pre-dry it, and then cure it to form a hydrophilic anti-fog layer. S7. Anneal the three-layer structure obtained in step S6 to obtain the flexible PC lens for the isolation positive pressure protective clothing.
12. The method for preparing the flexible PC lens for isolation positive pressure protective clothing according to claim 11, characterized in that: The curing process includes ultraviolet light curing or thermal curing.
Citation Information
Patent Citations
Preparation method of wear-resistant anti-fog PC optical spectacle lens
CN118085375A
Positive-pressure anti-fog mask and protective clothing with same
CN216315720U
